Lesson learned from the pandemic: Isolation and hygiene measures for COVID-19 could reduce the nosocomial infection rates in oncology wards. (December 2022) - Guven, Deniz C; Eroglu, Imdat; Ismayilov, Rashad; Ulusoydan, Ege; Aktepe, Oktay H; Telli Dizman, Gulcin; Arik, Zafer; Dizdar, Omer; Unal, Serhat; Metan, Gokhan; Kertmen, Neyran
Introduction: It was previously demonstrated that seasonal influenza incidence was significantly decreased during the COVID-19 pandemic, possibly due to respiratory and hygiene precautions. From this point, we hypothesized that the COVID-19 precautions could lead to a decrease in nosocomial infection rates in oncology inpatient wards. Methods: We evaluated the nosocomial infection rates in an inpatient palliative oncology ward in the first 3 months of the COVID-19 pandemic in our country and compared this rate with the same time frame of the previous year in our institution. Results: The percentage of nosocomial infections complicating the hospitalization episodes were significantly reduced in the first 3 months of the pandemic compared to the previous year (43 vs. 55 nosocomial infection episodes; 18.6% vs. 32.2%, p  = 0.002). The decrease in the nosocomial infections was consistent in the different types of infections, namely pneumonia (4.8% vs. 7.6%), urinary tract infection (5.2% vs. 7.6%), bacteremia (5.2% vs. 7%) and intraabdominal infections (2.6% vs. 3.5%). The median monthly disinfectant use was significantly increased to 98 liters (interquartile range: 82 – 114) in 2020 compared to 72 L (interquartile range: 36 – 72) in 2019 ( p  = 0.046). Conclusion: The continuation of the simple and feasible hygiene and distancing measures for healthcare workers and patient relatives and adaptations for earlier discharge could be beneficial for preventing nosocomial infections in oncology wards. These measures could be implemented routinely even after the COVID-19 pandemic for patient safety, especially in settings with higher nosocomial infection rates like inpatients palliative care units.